Application of Box-Behnken Design with Response Surface Methodology to Analyse Friction Characteristics for Corrugated Pipe via CFD - Azman A.; Yusoff M.Z.; Mukhtar A.; Gunnasegaran P.; Ching N.K.; Md Yasir A.S.H. (Semarak Ilmu Publishing, 2024)
Due to the fact that modern technologies are getting smaller and more compact and are anticipated to perform better, there has been an increase in interest in heat transfer enhancement employing hybrid nanofluids in tubes and channels in recent years. This study seeks to establish an outward saw tooth corrugated wall model-based predictive friction characteristic for internal tube flow. Computational Fluid Dynamics (CFD) was used to simulate the model numerically. The response behaviour study was then conducted utilising the Design of Experiment (DOE) and the Response Surface Methodology (RSM). The established surrogate model has led to the consideration of RSM. In this study, the DOE was executed by utilising the Box-Behnken Design (BBD) method with two-level factorial by considering three parametric factors which are: (a) 10000 to 30000 axial Reynolds number, Re, (b) 1mm to 4mm wave amplitude, a, and (c) 5mm to 20mm wavelength, lw. The results showed that the expected response surface values are consistent with the CFD values and that the predictive model is therefore reliable. The R-squared (R2) value is 98.25%, indicating that the model can predict new observations. The wavelength and wave amplitude show significant factors influencing the friction factor which is-0.11235 and 0.14861 respectively and this is based on the normal plot of the effect from the regression model from RSM. These results provide data for estimating the geometric characteristics of tube corrugated wall. 2023, Semarak Ilmu Publishing. All rights reserved.